The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/adfm.201802944
|View full text |Cite
|
Sign up to set email alerts
|

Built‐In Haze Glass‐Fabric Reinforced Siloxane Hybrid Film for Efficient Organic Light‐Emitting Diodes (OLEDs)

Abstract: Substrates with high transmittance and high haze are desired for increasing the light outcoupling efficiency of organic light‐emitting diodes (OLEDs). However, most of the polymer films used as substrate have high transmittance and low haze. Herein, a facile route to fabricate a built‐in haze glass‐fabric reinforced siloxane hybrid (GFRH) film having high total transmittance (≈89%) and high haze (≈89%) is reported using the scattering effect induced by refractive index contrast between the glass fabric and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…The neutral plane is linearly shifted from the center as the glass fabric is moved, implying that asymmetric impregnation of the glass fabric could be required to reduce the maximum tensile strain under bending. This is opposed to the symmetric structure of the conventional glass fabric–reinforced substrate [ 22–26 ] (see Figure S1, Supporting Information, for a detailed calculation procedure for the neutral plane shift).…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…The neutral plane is linearly shifted from the center as the glass fabric is moved, implying that asymmetric impregnation of the glass fabric could be required to reduce the maximum tensile strain under bending. This is opposed to the symmetric structure of the conventional glass fabric–reinforced substrate [ 22–26 ] (see Figure S1, Supporting Information, for a detailed calculation procedure for the neutral plane shift).…”
Section: Resultsmentioning
confidence: 90%
“…Figure a shows the fabrication process of the 80 μm thick GFRH substrate with a controlled neutral plane (GFRH‐CNP). Glass fabric was used for neutral plane control, and a transparent ESH [ 25,26 ] was used to match the refractive index with the glass fabric for high transparency of the fabricated substrate. First, (i) ESH resin was impregnated on the glass fabric, and then (ii) roll lamination and pre‐UV curing were conducted to fix the glass fabric position.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the internal structures can result in high efficiency improvement, a careful implementation must be done to ensure electrical stability of the OLEDs. Another possibility is to directly embed scattering structures in the substrate 1518 .…”
Section: Introductionmentioning
confidence: 99%
“…Lim et al 17 reported that while processing the fabrics at wet zone from pretreatment to finishing, the problem of shrinkage may be occurred due to uneven tension either by the mercerizing operation or by the stenter chain.…”
Section: Introductionmentioning
confidence: 99%